2005
DOI: 10.1162/0898929053467631
|View full text |Cite
|
Sign up to set email alerts
|

An Event-related Potential Study of Selective Auditory Attention in Children and Adults

Abstract: Abstract& In a dichotic listening paradigm, event-related potentials (ERPs) were recorded to linguistic and nonlinguistic probe stimuli embedded in 2 different narrative contexts as they were either attended or unattended. In adults, the typical N1 attention effect was observed for both types of probes: Probes superimposed on the attended narrative elicited an enhanced negativity compared to the same probes when unattended. Overall, this sustained attention effect was greater over medial and left lateral sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
139
3
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(164 citation statements)
references
References 78 publications
(119 reference statements)
21
139
3
1
Order By: Relevance
“…A stronger attention selectivity of the left hemisphere has been observed in previous studies in the visual (Reuter-Lorenz et al, 1990;Zani and Proverbio, 1995) and auditory (Coch et al, 2005) modalities. In the auditory modality, Alcaini et al (1995) have suggested that the left hemisphere could be preferentially involved in voluntary, selective attention whereas the right hemisphere would be more engaged in automatic attentional orientation to unexpected stimuli.…”
Section: Hemispheric Specializationsupporting
confidence: 73%
“…A stronger attention selectivity of the left hemisphere has been observed in previous studies in the visual (Reuter-Lorenz et al, 1990;Zani and Proverbio, 1995) and auditory (Coch et al, 2005) modalities. In the auditory modality, Alcaini et al (1995) have suggested that the left hemisphere could be preferentially involved in voluntary, selective attention whereas the right hemisphere would be more engaged in automatic attentional orientation to unexpected stimuli.…”
Section: Hemispheric Specializationsupporting
confidence: 73%
“…Attention related amplitude changes of the N1 potential have frequently been reported in literature (Hillyard et al 1973;Janata 2001;Näätänen et al 1978, Näätänen 1979Coch et al 2005; Thornton et al 2007;Müller et al 2003). Differences in N1 amplitude between tinnitus and non tinnitus subjects have also been shown by Jacobson et al (1996) and Jacobson and McCaslin (2003).…”
Section: Introductionmentioning
confidence: 69%
“…Depending on the emotional load of the tinnitus signal which defines its salience attention can be shifted more (low tinnitus related distress) or less (high tinnitus related distress) to the task. As the N1 wave of the ERP (Hillyard et al 1973;Coch et al 2005;Poghosyan and Ioannides 2008;Thornton et al 2007) is influenced by attention this results in higher differences in N1 amplitude between the attended and unattended stimulus conditions in patients with low tinnitus related distress as compared to patients with high distress.…”
Section: How Can This Results Be Interpreted In Light Of Existing Modementioning
confidence: 99%
“…The N1 is mostly sensitive to sound audibility and salience and parallels behavioral sound detection thresholds (Martin et al, 1997). Based on its known functional significance in adults as well as late emergence and specific elicitation conditions in children (long inter-stimulus intervals, ISI), we have suggested (Èeponienë et al, 2002; Èeponienë et al, 2005) that, at least partially, the N1 emerges as a complementing and balancing mechanism to the development of focused and sustained attention (Gomes et al, 2000;Coch et al, 2005b;Wible et al, 2005). That is, the auditory N1 may reflect a "gate-keeping" mechanism for sensory information, which depends on the load and direction of the ongoing mental activity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we suggested that the auditory P2 might reflect a sensory-attentional interface that comes online years before the more effective, "shortcut" N1 mechanism becomes functional. Specifically, the P2 is sensitive to stimulus salience -increases in amplitude with longer ISIs (Williams et al, 2006), shows robust refractoriness effects in children and adults (Coch et al, 2005a), and enhances in amplitude during selective attention tasks (Coch et al, 2005b). On the other hand, to a certain degree the P2 also reflects content feature perception (Crowley and Colrain, 2004) -it was enhanced during a discrimination, as compared with detection, task (Novak et al, 1992) and was was larger in amplitude in response to 400-Hz tones than to 3000-Hz tones in neonates, toddlers, children, and adults (Wunderlich et al, 2006).…”
Section: Introductionmentioning
confidence: 99%